Correlation Body Mass Index (BMI) with Asthma Quality of Life - Anisa Rahmatia; Reviono .; Arif Suryawan (Nexus Kedokteran Klinik, 2015)
Background: The development of science and technology is not accompanied by decreasing prevalence of asthma. During the time, therapy success was only measured by peak expiratory flow rate, severity of symptoms, the need for other treatments, the amount of sputum and responsiveness of airway without noticed to the patients quality of life itself. The evidences suggest that increasing BMI play an important role in asthma quality of life. Therefore, it needs study about correlation BMI with asthma quality of life. Methods: This study is an observational study with cross sectional conducted in February March 2015 in BBKPM Surakarta. Sampling was done by purposive sampling. Subject to fill (1) bio-data form, (2) Questionnaire : Asthma Control Test (ACT) and Asthma Quality of Life Questionnaire (AQLQ). Treatment in respondent (1) Measurement height and weight. Data obtained by 103 subjects and analyzed using Spearman correlation through SPSS 20.00 for Windows. Result: This study shows the value of Spearman correlation r = -0,541; p < 0,05, which means there is a negative correlation was statistically significant between BMI and asthma quality of life among asthma controlled grup with a moderate correlation strength. Whereas among asthma uncontrolled grup shows the value of Spearman correlation r = -0,852; p < 0,05 which means there is a negative correlation was statistically significant between BMI and asthma quality of life with a very strong correlation strength. Conclusion: There is a moderate negative correlation and statistically significant between BMI and asthma quality of life among asthma controlled grup. And then there is a very strong negative correlation and statistically significant between BMI and asthma quality of life among asthma uncontrolled grup. Keywords: BMI, Asthma Quality of Life